Unlawful Occupation of Inner-City Buildings: A Constitutional Analysis of the Rights and Obligations involved - Strydom, Janke; Viljoen, Sue (Potchefstroom Electronic Law Journal, 2017)
The unlawful occupation of inner-city buildings in South Africa has led to a number of legal disputes between vulnerable occupiers and individual landowners that highlight the conflict between individuals’ constitutional right not to be evicted in an arbitrary manner and property owners’ constitutional right not to be deprived of property arbitrarily. The cause of this tension is a shortage of affordable housing options for low-income households in the inner cities, a fact which shows that the state is evidently struggling to give effect to its housing obligation embodied in section 26(1) and (2) of the Constitution. In the majority of cases the courts assume that any interference with private landowners’ rights beyond a temporary nature would be unjustifiable, but they do this without undertaking a proper constitutional analysis to determine whether a further limitation of the individual landowner’s property rights might be justifiable and non-arbitrary in the circumstances of each case. In general the courts can allow, suspend or refuse the eviction of unlawful occupiers, provided that the order does not amount to an arbitrary deprivation of property. Nevertheless, in some instances the arbitrary deprivation of property is unavoidable, despite the court’s best efforts to protect property entitlements. These eviction cases show the limits of the courts’ powers both to provide adequate solutions to protect owners’ property rights and to give effect to the constitutional housing provision. In the light of three eviction cases, namely Blue Moonlight, Modderklip and Olivia Road, this article explains the role of the court and the local authority, together with the entitlements and social obligations of inner-city landowners within the framework of the property clause, in order to analyse the constitutionality of the courts’ decisions and to suggest ways in which the inner-city housing shortage may be addressed more effectively. This article also considers how two foreign jurisdictions, namely England and the Netherlands, have managed the precarious relationship between urban landowners – who often allow buildings to decay and stand vacant – and the homeless. These jurisdictions provide innovative alternatives to the expropriation of the ownership of private inner-city properties for housing purposes. Similar measures, tailored to accommodate the South African constitutional, economic and socio-economic landscape, may be a welcome addition to the existing statutory powers of the local authorities tasked with combatting homelessness in urban areas.